Analysis of the Reduction in Corporate Income Tax Rates and PSAK 46 on Earnings Management - Rizki Alaika; Memed Sueb; Sony Devano (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The government has set a policy of reducing the Corporate Income Tax rate a year earlier than the Omnibus Law to deal with the impact of the Covid-19 pandemic that has hit Indonesia since March 2020. However, the reduction in corporate income tax rates can motivate company management to carry out earnings management in order to save the tax burden. The implication of PSAK 46 is related to earnings management issues, namely that many company management take advantage of flexibility opportunities in preparing financial statements with an accrual approach in order to get bonuses for performance by minimizing the income tax burden. This study aims to examine differences in earnings management before and after the reduction in corporate income tax rates, differences in earnings management of potential winning companies and potential losers, and the effect of PSAK 46 on earnings management. The research method used is a quantitative research method using different tests and multiple linear regression analysis. The independent variable in this study consisted of a decrease in corporate income tax rates and PSAK 46. The dependent variable in this study was earnings management. The sample of this research is 57 companies from various sectors listed on the Indonesia Stock Exchange in 2019–2020.  The results showed that there was a significant difference in Corporate Income Tax rates for winner companies and potential discretionary accruals companies . corporate income has a significant difference, and current tax and deferred tax liabilities have a significant negative effect on earnings management, while deferred tax assets have no significant effect on earnings management.